Poverty, Cybercrime and National Security in Nigeria - Tope Shola Akinyetun (Advanced Studies on Socio-Economy Development, 2021)
The number of people living in poverty in Nigeria continues to grow at an exponential rate, making Nigeria the poverty capital of the world. As a result, cybercrime has become a haven for youths. The festering of cybercrime increases the chances of cyberterrorism and proliferates radicalization and hate speech – all of which pose a danger to national security in Nigeria. This study adopts an analytic approach to explore the interplay between poverty, cybercrime, and national security in Nigeria. The findings reveal that poverty is a major driver of cybercrime in Nigeria, and cybercrime poses a serious threat to national security. It shows that, with the prevalence of poverty, deprivation, and inequality, many Nigerian youth turn to crime for creating Nigeria as their desired. Cybercrime undermines national security by exposing individuals to violence, cyberespionage, cyberstalking, and manipulation. The study, recommends that decisive policies targeted at reducing poverty should be developed in Nigeria and that youths should be educated on the dangers of cybercrime and its incapacitating effect on national security. Moreover, cybersecurity should be prioritized by the Cyber Advisory Council. Meanwhile, cybercriminals must be dealt with under the full force of the law, establishing justice and serving as a deterrent to perpetrators who intend to commit crimes. Keywords: Cyber Crime, National security, Poverty, Scam, Unemployment